PERAN PEREMPUAN PEDESAAN DALAM MENINGKATKAN PEREKONOMIAN KELUARGA DI KABUPATEN ACEH BESAR - Cut Farianah Oktari; Sartiyah Sartiyah (Fakultas Ekonomi dan Bisnis UNSYIAH, 2020)
AbstractThis study aims to determine the role of rural women in improving the family economy by looking at the contribution of family income in reducing poverty. This study analyzes the age, education, working time, wages, and types of women's work related to the role of women's income in the family economy. The data used are primary data, obtained from field observations. The sample used as many as 122 people using the Slovin Method. Samples are housewife women and data collection is done by interview using a questionnaire, and determination of the sample using a purposive sampling method. The analysis model is descriptive quantitative and qualitative, explaining the processed table and tabulated data. The results showed that rural women with higher education had a greater contribution in increasing family income and reducing poverty, while women with less education had less contribution in the family and reducing poverty.Keywords: Role of Women, Income, Family Economy